2008
DOI: 10.1186/1743-422x-5-96
|View full text |Cite
|
Sign up to set email alerts
|

HIV-2 neutralization by intact V3-specific Fab fragments

Abstract: The V3 region of both HIV-1 gp120 and HIV-2 gp125 surface glycoprotein has been described as a target for neutralizing antibodies. In this study a conformation-sensitive (3C4) and a linear site-specific (7C8) anti-HIV-2 V3 monoclonal antibody (mAb) were characterized. The neutralization capacity of the purified mAbs and their respective papain-generated Fab fragments was analyzed. The Fabs were further characterized by sequence analysis. Our results demonstrate that neither purified mAbs were capable of neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…conformation-sensitive (3C4) and a linear site-specific (7C8) and their respective papain-generated Fab fragments suggested that whole 7C8 and 3C4 MAbs were sterically hindered from neutralizing HIV-2. Alternatively the smaller size of Fab fragments capably accessed the virion surface V3 region (Sourial & Nilsson 2008). Further proceeding in this direction, the crystal structure of the Fab fragment of 7C8 was presented for structural analysis which showed a deep and narrow highly hydrophobic antigen-binding cleft (Uchtenhagen et al 2011).…”
Section: Conventional Attemptsmentioning
confidence: 99%
“…conformation-sensitive (3C4) and a linear site-specific (7C8) and their respective papain-generated Fab fragments suggested that whole 7C8 and 3C4 MAbs were sterically hindered from neutralizing HIV-2. Alternatively the smaller size of Fab fragments capably accessed the virion surface V3 region (Sourial & Nilsson 2008). Further proceeding in this direction, the crystal structure of the Fab fragment of 7C8 was presented for structural analysis which showed a deep and narrow highly hydrophobic antigen-binding cleft (Uchtenhagen et al 2011).…”
Section: Conventional Attemptsmentioning
confidence: 99%
“…Fab fragments of the monoclonal antibody 7C8 were prepared through limited digestion with papain (Sigma; Sourial & Nilsson, 2008). The reaction was carried out in 20 mM sodium phosphate buffer pH 7.4 containing 150 mM NaCl, 10 mM EDTA and 10 mM cysteine (Sigma).…”
Section: Purification Of 7c8 Fab Fragmentmentioning
confidence: 99%
“…The hybridoma cell line that expresses 7C8, classified as being of the IgG 1 subtype (Sourial & Nilsson, 2008), was originally isolated from mice immunized with a 15-mer peptide derived from the HIV-2 V3-loop region that includes the conserved stretch of residues FHSQ Size-exclusion chromatography of the purified murine antibody 7C8 following papain digestion. Preparative chromatography was carried out in 20 mM Tris-HCl pH 7.4 containing 150 mM NaCl using a Superdex 75 10/300 GL size-exclusion column with a flow rate of 0.5 ml min À1 .…”
Section: Production and Purificationmentioning
confidence: 99%
See 2 more Smart Citations